Comparison of groundwater recharge estimation techniques in an alluvial aquifer system with an intermittent/ephemeral stream (Queensland, Australia) - King, Adam C.; Raiber, Matthias; Cox, Malcolm E.; Cendón, Dioni I. (Hydrogeology journal, 2017)
This study demonstrates the importance of the conceptual hydrogeological model for the estimation of groundwater recharge rates in an alluvial system interconnected with an ephemeral or intermittent stream in south-east Queensland, Australia. The losing/gaining condition of these streams is typically subject to temporal and spatial variability, and knowledge of these hydrological processes is critical for the interpretation of recharge estimates. Recharge rate estimates of 76–182 mm/year were determined using the water budget method. The water budget method provides useful broad approximations of recharge and discharge fluxes. The chloride mass balance (CMB) method and the tritium method were used on 17 and 13 sites respectively, yielding recharge rates of 1–43 mm/year (CMB) and 4–553 mm/year (tritium method). However, the conceptual hydrogeological model confirms that the results from the CMB method at some sites are not applicable in this setting because of overland flow and channel leakage. The tritium method was appropriate here and could be applied to other alluvial systems, provided that channel leakage and diffuse infiltration of rainfall can be accurately estimated. The water-table fluctuation (WTF) method was also applied to data from 16 bores; recharge estimates ranged from 0 to 721 mm/year. The WTF method was not suitable where bank storage processes occurred.